Comparison of the Subgross Distribution of the Lesions in Invasive Ductal and Lobular Carcinomas of the Breast: A Large-Format Histology Study - Syster Hofmeyer; Gyula Pekár; Mária Gere; Miklós Tarján; Dan Hellberg; Tibor Tot (International Journal of Breast Cancer)
To compare the lesion distribution and the extent of the disease in ductal and lobular carcinomas of the breast, we studied 586 ductal and 133 lobular consecutive cancers. All cases were documented on large-format histology slides. The invasive component of ductal carcinomas was unifocal in 63.3% (371/586), multifocal in 35.5% (208/586), and diffuse in 1.2% (7/586) of the cases. The corresponding figures in the lobular group were 27.8% (37/133), 45.9% (61/586), and 26.3% (35/133), respectively. When the distribution of the in situ and invasive component in the same tumors was combined to give an aggregate pattern, the ductal carcinomas were unifocal in 41.6% (244/586), multifocal in 31.6% (185/586), and diffuse in 26.8% (157/586) of the cases. The corresponding figures in the lobular category were 15.0% (20/133), 54.2% (72/133), and 30.8% (41/133), respectively. Ductal cancers were extensive in 45.7% (268/586), lobular in 65.4% (87/133) of the cases. All these differences were statistically highly significant (). While the histological tumor type itself (ductal versus lobular) did not influence the lymph node status, multifocal and diffuse distribution of the lesions were associated with significantly increased risk of lymph node metastases in both ductal and lobular cancers.